Factors Affecting Consumer Adoption of Mobile Financial Technology in Nepal - Sigdel, Shreedip (PYC Nepal Journal of Management, 2024)
This paper explores the factors that influence consumer adoption and continued usage of mobile financial technology, focusing on six key areas: individual awareness, perceived usefulness and ease of use, perceived risk, perceived benefits, cost, and government policies. The study addresses a gap in understanding how active users prioritize these factors for sustained usage. The sample includes active users of mobile financial services. The findings show that perceived benefits, cost, and government policies preventing fraud are the most important factors for continued use. While users are aware of risks, these do not impact their usage. Other factors, such as awareness and ease of use (user-friendliness), were found to play no significant role. The results suggest that trial usage of new products is crucial for adoption. If users understand the risks, recognize the benefits, and find the product practical and reliable, they are more likely to adopt and continue using it.